Coordination-driven discrete metallo-supramolecular assembly for rapid and selective photochemical CO2 reduction in aqueous solution. Issue 18 (20th April 2021) - Wang, Yanan; Chen, Longxin; Liu, Ting; Chao, Duobin
Abstract : A discrete metallo-supramolecular assembly bearing six iron(ii ) centers and twelve terpyridine fragments has been developed for highly efficient and selective photochemical CO2 reduction with an organic TADF photosensitizer. Abstract : A discrete metallo-supramolecular assembly composed of six iron(ii ) cations and twelve redox-active terpyridine fragments has been developed for the highly efficient visible-light-driven reduction of CO2 to CO with a TON of 14 956 and 99.6% selectivity in the presence of an organic thermally activated delayed fluorescence (TADF) photosensitizer 4CzIPN in aqueous solution. The photochemical system proceeds rapidly with a turnover frequency (TOF) of 276 min −1 . It is demonstrated that the redox-active terpyridine fragments in the assembly are reduced by the photosensitizer which could further act as an electron reservoir for CO2 reduction, resulting in the highly efficient reduction of CO2 . This work shows that discrete metallo-supramolecular assemblies could be used for robust photochemical CO2 reduction.